Rancang Bangun Sistem Informasi Disposisi Surat Berbasis Web (Studi Kasus Kementerian Pekerjaan Umum) - Sapto Aji; Migunani .; Fitro Nur Hakim (APMMI - Asosiasi Profesi Multimedia Indonesia, 2014)
Abstract : Disposition letter is part of the management of the official scripts which are important in an agency. Disposition letter giving written instructions regarding the completion of the follow-up letter or official script given by the leader to staff according to their expertise. Disposition process that conduct manually have a problems which is requiring the presence of the leader in the office to sign the order sheet disposition so that disposition process can be continued. The purpose of the Information Systems of Disposition Letter is to solve the problems occurred regarding the disposition letter in the agency. The system is made up of web-based information system that can be accessed on line. This system has a user-friendly with multiple roles, each role has a different authority. Pimpinan role has the authority to make the disposition, Sekretaris role has the authority to enter the incoming mail, Unit role has the authority to appoint staff to follow up the provisional disposition and Staff role has the authority to receive disposition to be implemented. Information Systems of Disposition Letter proved can be used to help simplify the management of the Ministry of Public Work’s letter. The system increases security because it can only be accessed by users who have registered, it allowed on line accessing, it is easier in the recording of incoming mail, faster to search a letter, the letter can be archived digitally into a database and provide disposition letter even when the leader is not in the office.Keywords : Information System, Disposition Letter, Web based